PENGARUH PERBEDAAN PENAMBAHAN KONSENTRASI WORTEL TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK KERUPUK WORTEL - Febriani, Veronika Devina; Surjoseputro, Sutarjo; Suseno, Thomas Indarto Putut (Widya Mandala Surabaya Catholic University, 2013)
Crackers is food product that most people favored and made from wheat starch with the addition of other ingredients and food additives are permitted. Carrot (Daucus carota L.) is one type of vegetable that can be varied in the manufacture of crackers. Beside, the relatively abundant production of carrots, the high nutrition like vitamin and mineral, its high water content of about 88.2% make carrot needs to use in processed food products, one of them is in crackers production. Raw materials used in this study is tapioca, flour, and fresh carrots, while the additional materials used are double-acting baking powder, garlic, salt, sugar, and mineral water. The study design used was Randomized Design Group non-factorial with one factor, namely the concentration of carrot which consists of 6 (six) standard of treatment, the concentration of carrot 0%, 10%, 20%, 30%, 40%, and 50 %. Each treatment was repeated 4 (four) times. The results showed that differences of carrot addition make real effect on water content, percentage expantion, bulk density of fried crackers, hardness, color (objective), and organoleptic testing (levels favorite color) carrot crackers. The higher addition of carrot will increase the bulk density of fried crackers, hardness, redness, and yellowness point of carrot crackers, but it will decrease the water content, percentage of expantion, lightness, and levels favorite color of carrot crackers. The 40% carrot addition produce carrot crackers with the best reception characteristics with point acceptability of color 5,58, crispiness 6,06, percentage of expantion 625,00%, hardness 610,241 N/s, and acceptability of taste is 6,06.